Is value added re-shored, near-shored or friend-shored? - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
We examine the latest trends in the geographical distribution of value added of final demand and production chains of the US, EU and China based on recently published international input-output tables extending to 2024. Both in final demand and in production chains the share of domestic value added tended to increase during the Covid-19 pandemic but then turned again to decline. In many cases the share of domestic value added has declined even to a lower level than in the beginning of the time period. Our analysis of geographical shifts of imported value added points to some signs of "near-shoring" and potential "friend-shoring" for all the economies, but the trends are not unambiguous.
urn:nbn:fi-fe20251126111662
Keywords: 330; global value chains; value-added trade; input-output